2011
DOI: 10.1080/02640414.2010.526626
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric exercise-induced muscle damage dissociates the lactate and gas exchange thresholds

Abstract: We tested the hypothesis that exercise-induced muscle damage would increase the ventilatory (V(E)) response to incremental/ramp cycle exercise (lower the gas exchange threshold) without altering the blood lactate profile, thereby dissociating the gas exchange and lactate thresholds. Ten physically active men completed maximal incremental cycle tests before (pre) and 48 h after (post) performing eccentric exercise comprising 100 squats. Pulmonary gas exchange was measured breath-by-breath and fingertip blood sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 39 publications
2
23
1
Order By: Relevance
“…Our findings that participants were unable to reach similar heart rates at exercise cessation combined with similar reductions in strength and V˙ O 2 peak (∼10%) suggest reduced strength and/or motivational factors rather than direct impairments of cardiorespiratory or mitochondrial function may be at play. Consistent with this idea, EIMD leads to heightened ratings of perceived exertion (RPE) (Black and Dobson, 2013;Burt et al, 2012Burt et al, , 2013Davies et al, 2009Davies et al, , 2011bGleeson et al, 1995;Twist and Eston, 2009) and heightened ratings of muscle pain (Black and Dobson, 2013) in humans during exercise.…”
Section: Introductionmentioning
confidence: 67%
“…Our findings that participants were unable to reach similar heart rates at exercise cessation combined with similar reductions in strength and V˙ O 2 peak (∼10%) suggest reduced strength and/or motivational factors rather than direct impairments of cardiorespiratory or mitochondrial function may be at play. Consistent with this idea, EIMD leads to heightened ratings of perceived exertion (RPE) (Black and Dobson, 2013;Burt et al, 2012Burt et al, , 2013Davies et al, 2009Davies et al, , 2011bGleeson et al, 1995;Twist and Eston, 2009) and heightened ratings of muscle pain (Black and Dobson, 2013) in humans during exercise.…”
Section: Introductionmentioning
confidence: 67%
“…2, 1-[1]) 20,21) . As a result, effort sense during the same exercise increases after ECC compared with that before conducting ECC [11][12][13]15,35) . Since Williamson et al 36) suggested that effort sense is closely related to central command, central command might be augmented as a result of the loss of muscle strength after ECC (Fig.…”
Section: Origin Of the Phase I Ventilatory Responsementioning
confidence: 99%
“…On the other hand, in comparable concentric contractions yielding a similar metabolic response, hyperventilation has been observed during ECC 10) , though the slope of the relationship between ventilation and arterial blood CO2 partial pressure in concentric exercise and that in ECC are almost the same 9) . Regarding the effect of a prior bout of ECC on ventilatory response to exercise, some investigators reported that the response at phases II and III during constant load or incremental exercise a few days after ECC was exaggerated [11][12][13][14][15] . Gleeson et al 13) and Schneider et al 14) suggested that this phenomenon is due to ventilatory compensation for greater blood lactacidosis after ECC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this muscle fiber disruption can also increases noxious (e.g., bradykinin, prostaglandin, hydrogen ions) stimuli (Clarkson and Hubal, 2002), which could stimulate group III/IV metabo-sensitive afferent fibers responsible for feedback to the brain (Amann et al, 2010) and explain EIMD derived pain (i.e., delayed onset muscle soreness). This muscle soreness could be associated with an increased sense of effort during MIE exercise (Davies et al, 2011) as a result of an increase in motor unit recruitment following EIMD (Eston et al, 2000). Damage to selective fibers may require additional motor units to be recruited in order to achieve the same force output, which could increase an individual's perception of effort (Braun and Dutto, 2003).…”
Section: Introductionmentioning
confidence: 99%